Applying structured computer-assisted collaborative concept mapping to flipped classroom for hospitality accounting. (June 2020) - Chiou, Chei-Chang; Tien, Li-Chu; Tang, Yu-Cheng
Abstract: This research investigates the effect of structured computer-assisted collaborative concept mapping (SCACCM) on student learning performance and motivation when it is used as an in-class auxiliary tool for flipped classroom teaching (FCT). This study adopts a quasi-experimental design. The teaching experiment is 3 h per week for 6 weeks, 114 students from a private university's hospitality management department in Taiwan. The experiment results show FCT strategy is helpful for enhancing students' learning motivation and academic achievements; using SCACCM as an auxiliary strategy for FCT is more effective in enhancing student learning motivation and achievements compared to a traditional exercise and discussion strategy.